RELEVANSI ARSIP DAN SEJARAH DALAM PROSES PEMBENTUKAN KARAKTER BANGSA - syah, Alam (HUMANIKA, 2014)
Abstract History as the past event, its tracking can be traced through the history trace. History trace is the fact and sign of history record which requires archives to disclosure. Archives as the history document is a silent witness which give evidence toward the success, failure, growth, and wealth of a nation. Archives, as past event record and a historical reconstruction, have an important role in building the nation character. The good nation character that contained in archives will strengthen the spirit of national anthem. Archive as the historical reconstruction can teach us a noble value, goodness, nasionalism, and teach us to followÂ  the struggle value of the national heroes to free the nation from ivanders suppression. When archives that full of patriotism and nasionalism values are served to people, it will grow the collective consciousness of Indonesia that has ever had a strong character in struggling to achieve its independence. Therefore, correlation between archive and history in forming the national character relates to archives role as the historical values ( values of historical). Archive is an ambassador of its era which can give informations for the next eraâ€™s interest. Thus, history is actually not inanimatte object. It is a building â€œliveâ€ that has many wise messages to deliver. Keywords: archive, history, forming, character, nation.